MANAJEMEN PEMBELAJARAN DALAM PENGEMBANGAN KOMPETENSI PESERTA DIDIK DI PONDOK MODERN DARUSSALAM GONTOR KAMPUS 7 KALIANDA LAMPUNG SELATAN - Iqbal Mustofa Fathurrahman; Oki Dermawan; M Kharis Fadillah (STKIP Pesisir Selatan, 2026)
Twenty-first-century education requires students not only to master knowledge but also to develop critical thinking, creativity, communication, and collaboration skills. In this context, learning management plays an important role in developing students’ competencies in cognitive, affective, and psychomotor domains through systematic and sustainable learning processes. This study aims to analyze learning management in developing student competencies at Pondok Modern Darussalam Gontor Campus 7 Kalianda, South Lampung. The study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the director of KMI, teaching staff, teachers, homeroom teachers, and students. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that: (1) learning planning was carried out through the formulation of objectives, preparation of learning materials and methods, and the design of learning programs; (2) learning organizing was implemented through the distribution of teacher roles, learning coordination, and the provision of learning resources; (3) learning implementation was conducted through integrative learning, character and value inculcation, and practical learning programs; and (4) learning supervision was conducted through continuous evaluation and supervision to support the development of student competencies.